2016
DOI: 10.1111/ner.12446
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Pallidal and Subthalamic Deep Brain Stimulation on Urologic Function in Parkinson’s Disease

Abstract: Objective Deep Brain Stimulation (DBS) is an established adjunctive surgical intervention for treating Parkinson’s disease (PD) motor symptoms. Both surgical targets, the globus pallidus interna (GPi) and subthalamic nucleus (STN), appear equally beneficial when treating motor symptoms but effects on nonmotor symptoms are not clear. Lower urinary tract symptoms (LUTS) are a common PD complaint. Given prior data in STN-DBS, we aimed to further explore potential benefits in LUTS in both targets. Methods We per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 35 publications
(99 reference statements)
3
28
1
Order By: Relevance
“…Both of these structures transfer striatal information to downstream thalamic nuclei, namely, the ventral anterior and ventral lateral nuclei, and from there to the frontal cortex, supplementary motor area, and dorsolateral prefrontal cortex. 20 Although STN-DBS has been shown to have positive benefits by improving abnormal urodynamic parameters in PD patients with lower urinary tract symptoms, 21 there have been cases in the literature where stimulation has resulted in significant urinary dysfunction. Fritsche and colleagues 22 reported 2 patients who developed acute urinary retention following STN-DBS, most likely attributed to suboptimal positioning of the electrodes.…”
Section: Urinary Domainmentioning
confidence: 99%
See 1 more Smart Citation
“…Both of these structures transfer striatal information to downstream thalamic nuclei, namely, the ventral anterior and ventral lateral nuclei, and from there to the frontal cortex, supplementary motor area, and dorsolateral prefrontal cortex. 20 Although STN-DBS has been shown to have positive benefits by improving abnormal urodynamic parameters in PD patients with lower urinary tract symptoms, 21 there have been cases in the literature where stimulation has resulted in significant urinary dysfunction. Fritsche and colleagues 22 reported 2 patients who developed acute urinary retention following STN-DBS, most likely attributed to suboptimal positioning of the electrodes.…”
Section: Urinary Domainmentioning
confidence: 99%
“…A further study by Mock and colleagues 21 analyzed the lower urinary tract symptoms in PD patients undergoing STN (n = 20) and GPi (n = 13) DBS. They found that urologic quality of life scores improved overall following DBS.…”
Section: Urinary Domainmentioning
confidence: 99%
“…The studies by Herzog and Seif in relation to subthalamic stimulation were prospective before/after and Porter conducted a clinical trial in the field of thalamotomy. Mock, Roy, and Witte conducted a studies in the field of Deep Brain Stimulation (DBS). The first was prospective before‐after, the second was prospective non‐blinded clinical trial and the third was randomized clinical trial.…”
Section: Resultsmentioning
confidence: 99%
“…114,115 Improvement in lower urinary tract symptoms in PD patients has also been documented following deep brain stimulation surgery targeting the subthalamic nucleus. 116…”
Section: Irritative Symptomsmentioning
confidence: 99%